2001
DOI: 10.1046/j.1365-2133.2001.04081.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to activated protein C due to factor V Leiden mutation: high prevalence in patients with post-thrombotic leg ulcers

Abstract: In view of this high prevalence of APC resistance of 36%, which has never previously been reported, patients with post-thrombotic leg ulcers should be investigated for APC resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
2
25
0
2
Order By: Relevance
“…However, available information concerning the relation between thrombophilia and PTS is limited and still controversial. While some authors failed to demonstrate any correlation between thrombophilia and PTS, others suggested a role of inherited thrombophilia and mainly factor V-Leiden mutation in the development of PTS and leg ulcers [46][47][48]. PTS is commonly reported among patients with proximal DVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, available information concerning the relation between thrombophilia and PTS is limited and still controversial. While some authors failed to demonstrate any correlation between thrombophilia and PTS, others suggested a role of inherited thrombophilia and mainly factor V-Leiden mutation in the development of PTS and leg ulcers [46][47][48]. PTS is commonly reported among patients with proximal DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Factor V Leiden mutation is a common risk factor for deep venous thrombosis as well as for recurrent leg ulceration [2]. There is also evidence that the factor V Leiden mutation, presumably due to thrombosis of placental vessels, may account for some cases of unexplained recurrent pregnancy loss [9].…”
Section: Discussionmentioning
confidence: 99%
“…Erst durch sorgfältige weitere Untersuchungen konnte aufgedeckt werden, dass nur eine Minderheit der Patienten außer der chronischen Veneninsuffizienz keine weiteren Grunderkrankungen hatte.Eine APC-Resistenz als Ursache einer Thrombose mit der Folge eines postthrombotischen Syndroms ist laut Literaturangaben bei 36% der Ulzera im Rahmen eines postthrombotischen Syndroms nachzuweisen sowie bei 6% der Ulzera durch eine Varikosis. Die APC-Resistenz wie auch die anderen bekannten Thrombophiliefaktoren kön-nen als Risikofaktor für die Entwicklung eines postthrombotischen Syndroms bei der Untersuchung von Ulkuspatienten berücksichtigt werden [9]. Da sich therapeutische Konsequenzen insbesondere für die Dauer der Antikoagulation in der Zeit nach akuter Thrombose ergeben,nur eingeschränkt jedoch bei der Therapie des Ulcus cruris, wurde die APC-Resistenz in dieser Studie nicht berücksichtigt.…”
Section: Schlussfolgerungunclassified